Total Phenolic, Flavonoids and Vitamin C Contents with Antioxidant Activity of Urtica dioica L. Leaves Growing in Zakho, Kurdistan Region-Iraq (Baghdad Science Journal, 2024)
The genus Urtica dioica L. (Urticaceae) is frequently grown in the Kurdistan region of Iraq and is used as a folk remedy by the locals to heal a variety of illnesses. The purpose of this study is to evaluate the total phenolic, flavonoid and vitamin C contents using spectrophotometric method with the determination of antioxidant activities for different solvents such as (aqueous, ethanol, ethyl acetate, chloroform and n-hexane) using different antioxidant methods namely (1,1-diphenyl-2-picrylhydrazyl, reducing power assay, total antioxidant capacity, nitric oxide scavenging, hydroxyl radical, β -carotene- Linoleic acid and iron chelating assays) and ascorbic acid as standard reference. Our results showed that polar solvent extracts exhibited a significant high phenolic and flavonoid contents while ethyl acetate extract had a high vitamin C content. In addition, the findings showed that the extracts had remarkable antioxidant effects compared with standard ascorbic acid. The ethanol extract of Urtica dioica L. leaves had stronger scavenging activities than other solvent extracts for 1,1-diphenyl-2-picrylhydrazyl and hydroxyl radicals. Water extract exhibited higher antioxidant effect than other extracts for reducing power and nitric oxide scavenging assays while lower antioxidant activity for β -carotene/Linoleic acid and total antioxidant capacity tests. In contrast, non-polar hexane had the highest antioxidant activity for the iron chelating assay. The present study shows that Urtica dioica L. leaf extracts are a viable natural source of antioxidants and may be used in food products as well as nutraceutical applications.